Proportional counters equipped with thin B4C conversion layers for the detection of slow neutrons - Duarte, Nuno Filipe Viseu (2022)
Tese de Doutoramento em Engenharia Física, Instrumentação, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.